Al Islam Education Learning at Independent Curriculum-Based Inclusion Schools in Grade 2 SD Muhammadiyah 1 Kebomas - assiddiqi, Dimas Hasbi Assiddiqi; Abdul Haris; Syamsurizal Yazid (PT Inovasi Pratama Internasional, 2025)
Al Islam education is the foundation of all sciences in the formation of the nation's character, especially in school students labeled as Islamic. In this case, it is inseparable from Al Islam education for inclusion in elementary schools (SD). This study aims to analyze the concept of Al Islam education learning in an independent curriculum-based inclusion school in grade 2 of SD Muhammadiyah 1 Kebomas, and analyze the application of Al Islam education learning in an inclusive school based on an independent curriculum in grade 2 of SD Muhammadiyah 1 Kebomas. The researcher compiled this research using qualitative research methods, while the data collection techniques used in this study were observation, interview, and documentary techniques. The data analysis techniques used by the researcher are the Miles, Huberman, and Saldana models, which consist of three stages: data representation, data display, and conclusions. From the data collection and analysis techniques used by the researcher, it was found that the learning of Al Islam education in inclusive schools does not prevent Al Islam education from being taught to inclusion students; that is, in the application of Al Islam education, there are things that must be adjusted to the abilities of inclusion students, which is also in accordance with the independent curriculum applied in the 2nd grade of SD Muhammadiyah 1 Keboma